Ethnobotanical Study of Medicinal Shrubs and Herbs Used by Forest-Fringe Communities of Ghana - Michael Asigbaase; Linda Anaba; Daniel Adusu; Simon Abugre; Adisa Ayeley Musah; Collins Ayine Nsor; Daniel Akoto Sarfo (Scientifica)
Documenting and quantitatively assessing medicinal plants and indigenous knowledge in different social contexts is critical in providing nature-based solutions to contemporary issues. Therefore, our study quantitatively evaluated medicinal shrubs and herbs in forest-fringe communities of Ghana and tested the versatility, ecological apparency and sociodemographic traits and knowledge dynamics hypotheses. Structured questionnaires, interviews and field visits were used to conduct an ethnobotanical survey involving 78 respondents, selected based on random and snowball sampling techniques. The data were analysed using quantitative indices such as indigenous knowledge index (IKI), species use value (SUV), informant agreement ratio (IAR) and ethnobotanical importance value (EIV). To test the versatility and sociodemographic traits and knowledge dynamics hypotheses, linear mixed-effects regressions were conducted, while one-way ANOVA was used to test the ecological apparency hypothesis. The Jaccard dissimilarity index was used to assess the degree of uniqueness of diseases treated by plants. We found 69 medicinal shrubs and herbs, belonging to 35 plant families, used to treat 101 diseases in the study area. Paullinia pinnata L. recorded the highest SUV (18.2) values, whereas Momordica charantia L. recorded the highest EIV (22.326) values. We found support for the versatility and sociodemographic traits and knowledge dynamics hypotheses, but no support for the ecological apparency hypothesis. The IAR of the 16 disease categories evaluated in this study ranged from 0.50 to 0.77. The Jaccard index showed that diseases treated by using introduced or native plants were 65.6% dissimilar. Our findings have implications for the achievement of SDG 3 (good health and well-being). We concluded that sociodemographic traits influence ethnobotanical knowledge dynamics, while plants with multiple useful parts are the most versatile and recommend the conservation of biodiversity to enhance diversity of treatment options.